Kid power - Pfeffer, Susan Beth, 1948-; Grant, Leigh (New York : Scholastic, 1977)
Eleven-year-old Janie advertises to do odd jobs in her neighborhood and receives so much business, she hires her friends and becomes manager of the Kid Power Agency.
Library Journal.
School Library Journal.
School Library Media Quarterly (A.A.A.L.).
5.4
3-6
Keywords: Family life -- Fiction; Summer employment -- Fiction; Family life -- Fiction; Summer employment -- Fiction